Development of an Information Model for Industrial Robots Actuators - Matarneh, R.; Sotnik, S.; Deineko, Z.; Lyashenko, V. (IOSR, 2019)
This work aims to develop a classification model for drives actuators features depending on their feature. The proposed model consists of nine levels that include the most common actuators, which in turn will facilitate easy identification of relationships and ease of finding alternatives. On the basis of the proposed classification, an information model of actuator alternatives has been created, which reflects key information about them. The created model will provide an opportunity to reduce the design time of the actuators.
Keywords: Information, Model; Actuators; Industrial; Robots